Effect of thermal treatment on the physico-chemical properties of bioactive hydroxyapatite derived from caprine bone bio-waste. Issue 17 (1st December 2019) - Barua, Emon; Das, Apurba; Pamu, D.; Deoghare, Ashish B.; Deb, Payel; Lala, Sumit Das; Chatterjee, Sushovan
Abstract: This study reports the extraction of bioactive hydroxyapatite (HA) from caprine bone bio-waste using thermal decomposition technique. The role of thermal treatment of the bones (calcined at 700-1300 °C) on the chemical and physico-chemical properties of the derived HA has been investigated. The change in properties of the calcined bone specimens are compared with the raw bones. A highest of 59.8% yield is obtained for the bones calcined at 700 °C which decreases with an increase in calcination temperature. Raman spectroscopy shows that the ionic group in all the ceramic residues corresponds to HA and trace amounts of β-TCP and α-TCP. XRD results confirm the phase stability of HA up to 900 °C beyond which, HA partially decomposes into β-TCP and α-TCP. The crystallite size and crystallinity initially enhances to a maximum of 39.7 nm and 93.1%, respectively with an increase in calcination temperature up to 900 °C. Later, it decreases with a further rise in the temperature. Thermal analysis shows a three-step degradation process of the raw bones. The morphology observed from the FESEM micrographs is found to be porous. Porosity decreases and the grain size increases with an increase in the calcination temperature. A high Ca/P ratio is confirmed from EDS analysis which decreases with a rise in calcination temperature. FETEM micrographs reveal polycrystalline HA particles of size 1.23 × 0.95 μm. Enhancement in relative density and shrinkage is observed with a rise in calcination temperature. In vitro bioactivity test by SBF immersion for 7, 14, 21 and 28 days and test for weight loss for 3, 5, 7, 14, 21 and 28 days show the formation of an apatite layer and biodegradability of HA9 sample, respectively. The study concludes that caprine bones calcined at 900 °C yields bioactive and biodegradable HA with the most optimum properties suitable for tissue engineering applications. Graphical abstract: Image 1